Ankara, Tehran, Baghdad: Three varieties of Kemalist urbanism. (April 2014) - Houston, Christopher
Kemalism has been the guiding and justifying ideology of the Turkish Republic since its institution in 1923. That Kemalism is exclusive to Turkey is a mainstay of Kemalist self-perception. But was (or is) Kemalism as political practice pursued by other regimes in the region? This paper argues that Kemalism should also be understood as a project of urbanism, and that urban interventions into Ankara, Tehran and Baghdad in the 20th century transformed all three into Kemalist cities. To illustrate, I describe certain features of their spatial, symbolic and sensory re-organization. My concluding remarks address the radically divergent fate of Kemalist urbanism in the contemporary cities of Baghdad, Tehran and Ankara.